2018
DOI: 10.3389/fpsyg.2018.00318
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Difficulty in Identifying and Describing Feelings in Non-Suicidal Self-Injury Behavior (NSSI): Associations With Perceived Attachment Quality, Stressful Life Events, and Suicidal Ideation

Abstract: Objective: Core alexithymic features, such as the difficulty in identifying and describing feelings, are associated with poor attachment styles and emotional trauma, which influence the capacity to regulate affect. Additionally, emotional regulation has been found to be the most commonly identified function associated with non-suicidal self-injury behavior (NSSI) in adolescents as they attempt to modulate strong emotions. However, few studies have examined the link between difficulty in identifying and describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 61 publications
6
49
0
8
Order By: Relevance
“…These findings also confirm a previous report from Gatta et al (19) on a non-clinical population of adolescents: those engaging in self-harming had considerably more difficulty in recognizing and expressing their own and others' emotional states, suggesting a fundamental role for alexithymia in the onset of NSSI (19). Similar evidence comes from other research in Italy and New Zealand (23,24), suggesting that alexithymia is a risk factor for NSSI as a dysfunctional coping mode, as well as by neuroimaging studies using functional magnetic resonance imaging (25).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These findings also confirm a previous report from Gatta et al (19) on a non-clinical population of adolescents: those engaging in self-harming had considerably more difficulty in recognizing and expressing their own and others' emotional states, suggesting a fundamental role for alexithymia in the onset of NSSI (19). Similar evidence comes from other research in Italy and New Zealand (23,24), suggesting that alexithymia is a risk factor for NSSI as a dysfunctional coping mode, as well as by neuroimaging studies using functional magnetic resonance imaging (25).…”
Section: Discussionsupporting
confidence: 81%
“…An Italian study on a non-clinical adolescent population found a positive association between difficulty in identifying and describing one's feelings and NSSI behavior. It also found that dysfunctional relationships with peers and parents can raise the risk of NSSI and suicidal ideation, consequently impairing an adolescent's ability to identify their emotions (23).…”
Section: Introductionmentioning
confidence: 99%
“…That both alexithymia and sensory disturbances are predictive of self-injury in autistic people is consistent with the prevalence of these features in other self-harming populations, and with the relationship that both alexithymia and sensory differences show with internalizing symptoms and/or mental ill-health in autism [41][42][43][44][45][46]. Alexithymia is higher than average in adolescent selfharmers and is a well-known correlate of self-injury in clinical populations [47][48][49]. Sensory disturbances have been a topic of interest as pertains to self-injury in autistic children and teenagers with and without intellectual disability.…”
supporting
confidence: 54%
“…Although numerous studies have used similar frequency bands (e.g., Buser et al, 2019;Hasking, Boyes, Finlay-Jones, McEvoy, & Rees, 2019;Midkiff et al, 2018;Whitlock et al, 2013), this approach may result in reduced power or conflate potentially different degrees of NSSI. That said, extant measures that employ count report formats may inadvertently bias reports to favor particular frequency ranges by suggesting count metrics (e.g., 1, 5, 15 in Cerutti, Zuffianò, & Spensieri, 2018;0, 10, 100, 500 in Nielsen, Sayal, & Townsend, 2017). Similarly, studies of NSSI vary with regard to duration, with some studies assessing NSSI events during the prior year as in the current study (e.g., Hasking et al, 2019;Muehlenkamp, Xhunga, & Brausch, 2019), in the past month (e.g., Auerbach et al, 2014;Fox et al, 2019), or over the course of the respondent's life time (e.g., Cerutti et al, 2018).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…That said, extant measures that employ count report formats may inadvertently bias reports to favor particular frequency ranges by suggesting count metrics (e.g., 1, 5, 15 in Cerutti, Zuffianò, & Spensieri, 2018;0, 10, 100, 500 in Nielsen, Sayal, & Townsend, 2017). Similarly, studies of NSSI vary with regard to duration, with some studies assessing NSSI events during the prior year as in the current study (e.g., Hasking et al, 2019;Muehlenkamp, Xhunga, & Brausch, 2019), in the past month (e.g., Auerbach et al, 2014;Fox et al, 2019), or over the course of the respondent's life time (e.g., Cerutti et al, 2018). It is not yet clear if and how these variations may influence NSSI distributions and, by extension, the relative effectiveness of statistical approaches for addressing data skewness.…”
Section: Strengths and Limitationsmentioning
confidence: 99%